Health, economic, and social implications of COVID‐19 for China's rural population. (11th May 2021) - Wang, Huan; Dill, Sarah‐Eve; Zhou, Huan; Ma, Yue; Xue, Hao; Sylvia, Sean; Smith, Kumi; Boswell, Matthew; Medina, Alexis; Loyalka, Prashant; Abby, Cody; Friesen, Dimitris; et al.
Abstract: This study examines the effects of local and nationwide COVID‐19 disease control measures on the health and economy of China's rural population. We conducted phone surveys with 726 randomly selected village informants across seven rural Chinese provinces in February 2020. Four villages (0.55%) reported infections, and none reported deaths. Disease control measures had been universally implemented in all sample villages. About 74% of informants reported that villagers with wage‐earning jobs outside the village had stopped working due to workplace closures. A higher percentage of rural individuals could not work due to transportation, housing, and other constraints. Local governments had taken measures to reduce the impact of COVID‐19. Although schools in all surveyed villages were closed, 71% of village informants reported that students were attending classes online. Overall, measures to control COVID‐19 appear to have been successful in limiting disease transmission in rural communities outside the main epidemic area. Rural Chinese citizens, however, have experienced significant economic consequences from the disease control measures.